Driving Outside the Wire: Examining Factors Impacting Veterans' Postdeployment Driving. (October 2020) - Winter, Sandra; Jeghers, Mary; Reid, Emily; McGowan, Cassandra; Young, Mary Ellen; Classen, Sherrilene
Combat Veterans (CVs) deployed to Iraq or Afghanistan experience driving difficulty, based on medical conditions and/or deployment exposures, elevating their risk of motor vehicle crash-related injury or death. To address grounded theory rigor and incorporate constructs such as the Person Environment Occupation Performance model, we revised the Hannold et al. (2013) conceptual framework. We conducted two focus groups with seven CVs. Conceptual framework revisions were based on an iterative process and thematic analysis. We elicited CVs' perspectives on deployment training, driving pre- and postdeployment, strategies, and intervention preferences. Personal, environmental, and task factors underpinned CVs' driving. Participants described triggers (e.g., stressful stimuli), use of environmental (e.g., car controls) or personal (e.g., avoiding traffic) strategies, and outcomes of appropriate or risky driving. Findings illustrated CVs' driving difficulty and informed development of a Veteran-centric driving intervention. Improving driving fitness has implications for Veterans' participation and community integration.